1998
DOI: 10.1029/98wr00004
|View full text |Cite
|
Sign up to set email alerts
|

Approximation of asymptotic dispersivity of conservative solute in unsaturated heterogeneous media with steady state flow

Abstract: Abstract. The relation between the heterogeneity of hydraulic properties and effective asymptotic transport is studied for microscopically heterogeneous but macroscopically homogeneous unsaturated media with steady flow. Heterogeneity is described by the scaling of the hydraulic functions 0 (½m) and K(0). The study is based on an analytical approximation of asymptotic dispersivity under the assumption that matric potential is spatially constant. For the special case of a water-saturated medium the result of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…Hence, by introducing a small amount of gas, the high-end tail of the velocity distribution is cut off, and water flow in the porous medium becomes more uniform. On larger scales, these findings have been observed both by experimental findings and numerical studies [e.g., Birkholzer and Tsang, 1997;Hammel and Roth, 1998;Cirpka and Kitanidis, 2002].…”
Section: Dispersion and Gas Saturation Resultsmentioning
confidence: 55%
“…Hence, by introducing a small amount of gas, the high-end tail of the velocity distribution is cut off, and water flow in the porous medium becomes more uniform. On larger scales, these findings have been observed both by experimental findings and numerical studies [e.g., Birkholzer and Tsang, 1997;Hammel and Roth, 1998;Cirpka and Kitanidis, 2002].…”
Section: Dispersion and Gas Saturation Resultsmentioning
confidence: 55%
“…Early agricultural applications included simulations of various irrigation or drainage schemes (e.g., Benjamin et al, 1994; Meshkat et al, 1999) and the transport of various chemicals applied to agricultural soils (e.g., de Vos et al, 2000). Early nonagricultural applications included studies of flow and transport in heterogeneous porous media (e.g., Tseng and Jury, 1994; Roth, 1995; Roth and Hammel, 1996; Hammel and Roth, 1998). These studies showed that due to soil heterogeneity, water and solutes can find flow paths that are much more conductive than would be expected from the average hydraulic conductivity.…”
Section: Dos Numerical Modelsmentioning
confidence: 99%
“…There were essentially two features common to these studies (Hammel and Roth 1998). First, the local vertical dispersion of solute strongly appears to depend on the measuring volume; it is generally smaller for small volumes such as boreholes than for the volume at which results are desired.…”
Section: Technical Backgroundmentioning
confidence: 99%
“…Studies include transport tests in the United States at Las Cruces, New Mexico (Wierenga et al 1990;Hills et al 1991;Rockhold et al 1996); at Idaho National Engineering Laboratory in Idaho Falls, Idaho (Wood and Norrell 1996); and at Maricopa, Arizona (Young et al 1996). Studies outside of the United States include studies in Canada (Kachanoski et al 1990;van Wesenbeeck and Kachanoski 1994) and in Europe (Schulin et al 1987;Hammel and Roth 1998).…”
Section: Technical Backgroundmentioning
confidence: 99%